INFLUENCE OF SERVICE QUALITY AND PROMOTION ON PURCHASE DECISIONS IN PT ACE HARDWARE INDONESIA Tbk CABANG LIPO KARAWACI - Agung Tri Putranto (Yayasan Education and Social Center, 2022)
This study aims to determine how much service quality and promotion influence purchasing decisions at Pt Ace Hardware Indonesia Tbk Lipo Karawaci Branch. This research method is quantitative descriptive research and uses a data collection method using a questionnaire instrument. The population in this study amounted to 177,966 respondents, and the sample in this study amounted to 100 respondents and used a random sampling technique. At the same time, statistical formulas are used in the data analysis method, such as the instrument testing technique of validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, correlation coefficient test, coefficient of determination test, t-test, and f test. The findings of this study indicate that all validity tests are valid, all reliability tests are reliable, all normality tests are typically distributed, all multicollinearity tests are non-multicollinear, all heteroscedasticity tests are non-heteroscedastic, and all multiple linear regression tests are non-heteroscedastic. The regression equation Y = 8.564 + 0.443X1 + 0.360 X2 indicates that with a constant of 8,564, it states that without and from the results of the correlation coefficient of the Service Quality variable (X1) on the Purchase Decision, it is obtained that 0.619 is said to be strong. The correlation coefficient of the Promotion variable (X2) on Purchase Decisions got 0.613 is said to be strong. And the value of the correlation coefficient between Service Quality (X1) and Promotion (X2) on purchasing decisions is 0.719, so it is said to be strong. The coefficient of determination test obtained an R Square value of 0.518 or 51.8%, meaning that Service Quality and Promotion together had a positive effect on Purchase Decisions at Pt Ace Hardware Indonesia Tbk Lipo Karawaci Branch of 51.8%, and other variables influenced the remaining 48.2%. The t-test shows that Service Quality has a positive effect on Purchase Decisions at Pt Ace Hardware Indonesia Tbk Lipo Karawaci Branch with a t count > t table (7.810 > 1.660) and sig < 0.05 (0.000 < 0.05), then Ho is rejected, and Ha is accepted. The promotion has a positive effect on Purchase Decisions at Pt Ace Hardware Indonesia Tbk Lipo Karawaci Branch with a value of t count > t table (7.685 > 1.6614) and sig < 0.05 (0.000 < 0.05), then Ho is rejected, and Ha is accepted. The f-test of Service Quality and Promotion together has a positive effect on Purchase Decisions at Pt Ace Hardware Indonesia Tbk Lipo Karawaci Branch with f count > f table (52,042 > 3.09) and sig < 0.05 (0.000 < 0.05)